2019
DOI: 10.1002/hep4.1390
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspectives on Early Liver Transplantation in Alcohol‐Related Liver Disease

Abstract: Liver transplant programs in Canada require a period of 6 months of abstinence from alcohol before considering a patient with liver disease secondary to alcohol for transplantation. Although some studies have demonstrated good outcomes following a transplant in carefully selected patients before the 6‐month abstinence period has been met, there have been arguments against this, including the claim that the public has a general negative perception of those with alcohol dependence. We performed a multicenter cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The concept of a specific period of abstinence continues to be debated (17,18) and remains controversial, with potential legal implications (19). A survey of patients in British Columbia showed that 43% would be less trusting of the transplantation process if a period of abstinence was not maintained, and only 30.5% would support eliminating a specific period of abstinence altogether (20).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of a specific period of abstinence continues to be debated (17,18) and remains controversial, with potential legal implications (19). A survey of patients in British Columbia showed that 43% would be less trusting of the transplantation process if a period of abstinence was not maintained, and only 30.5% would support eliminating a specific period of abstinence altogether (20).…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, all transplant centers require 6-months of abstinence before listing patients with ARLD and early LT is still contraindicated in patients with severe AH (101). However, there is a desire to relax the criteria in selected patients who are unlikely to survive without transplantation, such as those with severe AH who do not respond to steroids (101,102). The Ontario ARLD Pilot Program, which was launched in 2018 to challenge the "6-month abstinence rule" (33) observed no significant differences in survival between patients transplanted through the program or after more than 6 months of abstinence and 6.8% of patients returned to alcohol use an average of 260 days after transplantation.…”
Section: Liver Transplantation For Severe Alcohol-related Hepatitis?mentioning
confidence: 99%
“…( 1 ) Although the use of donated livers for those with ALD is still not strongly supported by the public, a review of the United Kingdom Organ Donor Register shows no clear evidence that this lack of support translates into loss of donors. ( 2,3 ) Return to a damaging pattern of alcohol use is associated with a worse outcome, but graft loss from disease recurrence (that is, a return to alcohol) is low and less than that seen in many other indications for LT. ( 4,5 ) Thus, the debate is not about the ethics of access to LT of those with a self‐inflicted condition, but whether expanding the indication is in line with the best available evidence.…”
Section: Society Year Recommendationmentioning
confidence: 99%